2005
DOI: 10.1111/j.1463-1318.2005.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of faecal incontinence severity on health domains

Abstract: There exists a significant relation between severity of incontinence and frequency of reported problems in the domains of usual activities, pain/discomfort and anxiety/depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 37 publications
1
44
0
3
Order By: Relevance
“…8,27,31 It is suggested that the St. Mark's score reflects the impact of experiencing AI on the sufferers' well-being and that the association is dependent on the severity of symptoms. 34 Some authors indicate that increasing levels of frequency and quantity of incontinence have a negative impact on usual everyday activities as well as on general and sexual QoL in patients with long-standing AI. [34][35][36] The occurrence of incontinence episodes less than once a month is reported to have a lower impact on QoL than more frequent incontinence episodes; however, one study found monthly and weekly episodes of stool incontinence to be equally distressing for patients with long-standing AI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,27,31 It is suggested that the St. Mark's score reflects the impact of experiencing AI on the sufferers' well-being and that the association is dependent on the severity of symptoms. 34 Some authors indicate that increasing levels of frequency and quantity of incontinence have a negative impact on usual everyday activities as well as on general and sexual QoL in patients with long-standing AI. [34][35][36] The occurrence of incontinence episodes less than once a month is reported to have a lower impact on QoL than more frequent incontinence episodes; however, one study found monthly and weekly episodes of stool incontinence to be equally distressing for patients with long-standing AI.…”
Section: Discussionmentioning
confidence: 99%
“…34 Some authors indicate that increasing levels of frequency and quantity of incontinence have a negative impact on usual everyday activities as well as on general and sexual QoL in patients with long-standing AI. [34][35][36] The occurrence of incontinence episodes less than once a month is reported to have a lower impact on QoL than more frequent incontinence episodes; however, one study found monthly and weekly episodes of stool incontinence to be equally distressing for patients with long-standing AI. 35 In contrast to previous reports of flatus incontinence at any frequency being the least bothersome symptom of AI 31 , the findings in this study suggest that experiencing flatus incontinence alone on a weekly or daily basis has a profound negative impact on QoL, especially in the domain 'Embarrassment'.…”
Section: Discussionmentioning
confidence: 99%
“…FI can lead to social isolation. It also can adversely affect ability to maintain relationships, occupation and self-esteem aspects of the quality of life (QOL) [10,11] . Ulcerative colitis (UC) and Crohn's disease (CD) are chronic inflammatory conditions related to the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Debido al considerable efecto que tiene la IF en la calidad de vida (CV) de los pacientes tanto en el ámbito sicológico como social 9,10 , es importante encontrar los factores que condicionan esta patología. Lo anterior no es fácil de hacer ya que un alto número de pacientes afectados no consulta por el estigma que esta conlleva 11 .…”
Section: Discussionunclassified